Stoic defence of physician-assisted suicide - Tomasini, Floris (Acta Bioethica, 2014)
Rational suicide can be minimally defined as: instrumentally rational, autonomous, due to stable goals and not due to mental illness. One major problem with rational suicide is that it tends toward a technical psychiatric definition, excluding any philosophical explanation of why rational suicide could be ethically justified. In other words, there is a tendency towards an instrumental view of rationality which concentrates on safeguarding the rational means of suicide, rather than fully considering the rational ends of why suicide could be ethically justified in certain special and controlled circumstances. To begin, the plausibility of rational suicide is explored. Following on, the classical stoic idea of rational ends of suicide is then reframed for a more contemporary audience in the socially relevant context of physician-assisted suicide.